A transmuscular path of the medial branch of the high division of the median nerve: an anatomical variation of clinical and surgical importance - Kuhn, Caio Siqueira; Barros, Lucimário de Carvalho; Sant’Anna Aragão, Iapunira Catarina; Aragão, Felipe Matheus Sant’Anna; Reis, Francisco Prado; Mendonça, Deise Maria Furtado de; Aragão, José Aderval (Brazilian Journal of Case Reports, 2024)
The median nerve (MN) is a mixed nerve formed in the brachial plexus, which innervates a large part of the upper limb. It presents several variations in its trajectory, resulting in many pathologies and iatrogenic surgical compromises. This report highlights a transmuscular route of the medial branch of the upper division of the MN, which to date does not fit into the classifications described in the literature on MN variations. Knowledge of this high division of the MN, as well as its transfixation by the flexor digitorum superficialis muscle, is of fundamental importance in neuropathy syndromes due to entrapment of the MN, as well as in surgical guidance to prevent injuries. Late diagnosis of traumatic peripheral nerve injuries results in greater functional impairment and greater socioeconomic loss, especially in young patients. Therefore, timely identification is essential to minimize long-term consequences and improve the patient’s quality of life.